Negotiating Victim Protection in Aceh’s Qanun Jinayat: Judicial Reasoning in the Blangkejeren Sharia Court’s Rape Decision - Lukman AR; Andryan Andryan; Ruetaitip Chansrakaeo (Ahlika: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This article addresses a central tension in the adjudication of rape under Aceh’s Qanun Jinayat: a judgment may establish criminal responsibility and impose severe punishment while still leaving the victim’s procedural voice, recovery, and material redress underdeveloped. It examines Decision Number 25/JN/2025/MS.Bkj of the Blangkejeren Sharia Court to determine how the judges constructed the elements of rape, assessed evidence, treated the mahram relationship, and connected punishment to victim protection. The study uses normative legal research with statutory, case, conceptual, and comparative approaches. Primary materials include the court decision, Qanun Aceh Number 6 of 2014, Law Number 12 of 2022 on Sexual Violence Crimes, and Qanun Aceh Number 12 of 2025. The findings show that the court’s attribution of guilt rested on convergent facts, the defendant’s admission, repeated conduct, pregnancy, and a profound familial power imbalance. Nevertheless, the reasoning remained predominantly offender- and punishment-centred: it did not fully articulate the victim’s trauma, participation, restitution, long-term recovery, or protection from secondary victimization. The article therefore proposes a Victim-Centred Jinayat Justice model that combines Islamic commitments to dignity, justice, and prevention with trauma-informed procedure, non-stereotyped evidence assessment, victim voice, integrated remedies, and transparent proportionality review. The contribution lies in reframing the legitimacy of jinayat adjudication: it should be measured not only by the severity of ’uqubat, but also by the quality of the process and the completeness of remedies delivered to the victim. [Artikel ini membahas ketegangan mendasar dalam pemeriksaan tindak pidana pemerkosaan berdasarkan Qanun Jinayat Aceh, yaitu bahwa putusan dapat menetapkan pertanggungjawaban pidana dan menjatuhkan hukuman berat, tetapi tetap belum memadai dalam mengakomodasi suara prosedural, pemulihan, dan ganti kerugian korban. Penelitian menganalisis Putusan Mahkamah Syar’iyah Blangkejeren Nomor 25/JN/2025/MS.Bkj untuk menilai cara majelis hakim mengonstruksikan unsur pemerkosaan, mengevaluasi alat bukti, mempertimbangkan hubungan mahram, serta menghubungkan pemidanaan dengan perlindungan korban. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan, kasus, konseptual, dan perbandingan. Bahan hukum primer meliputi putusan pengadilan, Qanun Aceh Nomor 6 Tahun 2014, Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual, dan Qanun Aceh Nomor 12 Tahun 2025. Hasil penelitian menunjukkan bahwa penetapan kesalahan terdakwa ditopang oleh fakta yang saling menguatkan, pengakuan terdakwa, perbuatan berulang, kehamilan korban, dan ketimpangan kuasa dalam relasi keluarga. Namun, pertimbangan hukum masih dominan berorientasi pada pelaku dan penghukuman karena belum menguraikan secara memadai trauma, partisipasi, restitusi, pemulihan jangka panjang, dan pencegahan viktimisasi sekunder. Artikel ini menawarkan model Victim-Centred Jinayat Justice yang memadukan nilai Islam mengenai martabat, keadilan, dan pencegahan dengan prosedur berbasis trauma, penilaian bukti tanpa stereotip, suara korban, pemulihan terpadu, dan pengujian proporsionalitas yang transparan. Kontribusi penelitian terletak pada penegasan bahwa legitimasi peradilan jinayat tidak hanya diukur dari beratnya ’uqubat, tetapi juga dari kualitas proses dan kelengkapan pemulihan bagi korban.]